2019
DOI: 10.1200/jgo.18.00173
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib Plus Letrozole as First-Line Therapy in Postmenopausal Asian Women With Metastatic Breast Cancer: Results From the Phase III, Randomized PALOMA-2 Study

Abstract: PURPOSE In PALOMA-2, palbociclib plus letrozole significantly improved progression-free survival (PFS) as initial treatment of estrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer. We assessed the benefit of palbociclib plus letrozole in Asians. PATIENTS AND METHODS Of 666 enrolled postmenopausal women with estrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer (no prior treatment of advanced disease), 95 were Asian. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
79
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 17 publications
11
79
0
2
Order By: Relevance
“…The effect of palbociclib dose reduction on the frequency and severity of hematologic AEs regardless of ethnicity is supported by a previous analysis of PALOMA-2, in which higher rates of hematologic Table 3 Incidence of hematologic adverse events before/after palbociclib dose reduction from 100 to 75 mg AEs were observed in Asian versus non-Asian patients but were effectively managed with dose adjustments [17]. Higher rates of neutropenia may be due to a lower baseline ANC.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The effect of palbociclib dose reduction on the frequency and severity of hematologic AEs regardless of ethnicity is supported by a previous analysis of PALOMA-2, in which higher rates of hematologic Table 3 Incidence of hematologic adverse events before/after palbociclib dose reduction from 100 to 75 mg AEs were observed in Asian versus non-Asian patients but were effectively managed with dose adjustments [17]. Higher rates of neutropenia may be due to a lower baseline ANC.…”
Section: Discussionmentioning
confidence: 68%
“…Subgroup analyses of PALOMA-2 and PALOMA-3 also demonstrated that Asian and non-Asian patients had similar PFS outcomes, even though Asian patients had more dose reductions [17]. This finding is likely due to higher palbociclib exposure in Asian versus non-Asian patients because of lower palbociclib clearance in Asian patients [10,17]. Dose modification due to AEs does not appear to negatively impact the efficacy of palbociclib plus ET in patients with HR+/HER2− ABC, but does reduce the severity and incidence of AEs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Findings in the present study showed that clinical characteristics, such as Asian ethnicity and low baseline absolute neutrophil counts, may increase the risk of developing grade 3/4 neutropenia. Additionally, an analysis of the Asian subgroup in PALOMA‐2 revealed that Asian patients had lower mean and median baseline absolute neutrophil counts compared with non‐Asians . These observations highlight the importance of closely monitoring these patients and intervening with dose adjustments when indicated.…”
Section: Discussionmentioning
confidence: 95%
“…Von den sekundär metastasierten Pa tien ten sollten die primär oder de novo metastasierten Pa tien ten unterschieden werden, da es sich hier um In den letzten Jahren hat sich jedoch die Kombinationstherapie aus einer anti-hormonellen mit einer weiteren zielgerichteten Sub stanz als wesentlich wirksamer in der Behandlung des mBC herausgestellt. Neue Sub stanzen hemmen das Protein mammalian Target of Rapamycin (mTOR) oder die CDK4/6 [12][13][14][15][16][17]. Die im klinischen Alltag gängige Unterscheidung der beiden Subtypen Luminal A und B spielt jedoch für die Auswahl des Therapie ansatzes keine relevante Rolle.…”
Section: Fokus Her2-negatives Metastasiertes Mammakarzinomunclassified